Reading Strategies on the Ability to Read Narrative Texts and Explanatory Texts - I Made Hendra Sukmayasa; I Nyoman Sudiana; Ni Nyoman Kurnia Wati (Journal for Lesson and Learning Studies, 2023)
In general, our students' reading ability is still low. The aim of this research is to analyze the effect of learning reading strategies on the ability to read narrative texts and explanatory texts in fourth grade elementary school students. This research is a quasi-experimental research (quasi experiment). The research design used was a pretest-posttest control-group design. The population of this study was 111 students, while the sample in this study was 76 students. The independent variable in this research is learning reading strategies, while the dependent variable is students' ability to read narrative texts and students' ability to read explanatory texts. The data collection method used is the test method. The collected data on students' ability to read narrative text and ability to read explanatory text were analyzed using the MANOVA statistical analysis technique. Based on the research that has been conducted, it was found that first, there is a significant influence of learning reading strategies on the ability to read narrative texts of fourth grade elementary school students. Second, there is a significant influence of reading strategy learning on the ability to read explanatory texts of fourth grade elementary school students. Third, Simultaneously, there is a significant influence of reading strategy learning on the ability to read narrative texts and the ability to read explanatory texts in fourth grade elementary school students.